1985
DOI: 10.1111/j.1432-1033.1985.tb08861.x
|View full text |Cite
|
Sign up to set email alerts
|

3-C-Branched aldoses in lipopolysaccharide of phase I Coxiella buurnetii and their role as immunodominant factors

Abstract: Mild acid hydrolysis with 1% acetic acid (lOO°C, of lipopolysaccharide (LPS) isolated fromCoxiella burnetii phase I cells leads to a drastic decrease in its serological reactivity as shown by the passive hemolysis test. This decrease in reactivity occurs parallel or even prior to the cleavage of LPS into free lipid A and the polysaccharide moiety. During this mild hydrolysis two unusual sugars (X and Y) are released from the LPS, which were obtained in pure state by thin-layer chromatography. Analysis of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…These LPSs form bilayer membranes in aqueous solutions (Shands, 1971 ;Shands et al, 1967) with the polysaccharide moiety facing outwards. The hydrophilic and hydrophobic properties of phase I and phase I1 LPS, respectively (Schramek & Mayer, 1982;Amano & Williams, 1984;Schramek et al, 1985) suggest that the carbohydrate side chain contributes to the physico-chemical differences. Both LPSs from C. burnetii also formed the bilayer structures as shown in Fig.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…These LPSs form bilayer membranes in aqueous solutions (Shands, 1971 ;Shands et al, 1967) with the polysaccharide moiety facing outwards. The hydrophilic and hydrophobic properties of phase I and phase I1 LPS, respectively (Schramek & Mayer, 1982;Amano & Williams, 1984;Schramek et al, 1985) suggest that the carbohydrate side chain contributes to the physico-chemical differences. Both LPSs from C. burnetii also formed the bilayer structures as shown in Fig.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…The JB153-7 product has very good homology to fucose synthetase and should complete the synthesis of fucose from the 4-keto sugar by providing the GDP-mannose epimerasereductase (46% identity for most of the protein) activity necessary to effect epimerization of CH 3 at C-5 and epimerization of OH at C-3. However, the presence of fucose in C. burnetii LPS is doubtful, as none of the three independent groups of workers who previously studied the carbohydrate structure of this organism reported the presence of fucose (2,3,8,37). Fucose may be used elsewhere in the organism, such as in a colanic acid-like molecule (20,39,59) or in a capsular polysaccharide.…”
Section: -Oxoacid Dehydrogenases (Pyruvate or Acetoin)mentioning
confidence: 98%
“…Phase II LPS possesses 2-keto-3-deoxyoctulonosic acid (KDO), D-mannose, D-glycero-D-manno-heptose, lipid A or a lipid A analog, and a very complex mixture of fatty acids, many of which are branched (2,36,47,48,58). Phase I LPS also possesses these components but, in addition, has virenose, dihydrohydroxystreptose (3,37,47), and galactosaminuronyl-␣(1,6)-glucosamine (3). These observations are consistent with a smoothto-rough transition analogous to that seen in gram-negative enteric bacteria (2,13,17,36).…”
mentioning
confidence: 99%
“…However, some studies on the Coxiella LPSs have shown that the sugar composition and structure of polysaccharide moiety and lipid A content produce the unique banding profile on SDS-PAGE, and that three sugars galactosaminuronyl-α(1-6)-glucosamine, dihydrohydroxystreptose and virenose make up the dominant immunogenic and antigenic determinants [1,2,14,15,20]. Collectively, these results may indicate that sugar composition, size and shape of the O-specific polysaccharide chains on the LPSs of four groups are different to each other, although many epitopes are shared.…”
mentioning
confidence: 99%